Activity of essential oils of Lippia alba chemotypes and their major monoterpenes against phytopathogenic fungi - Magna Galvão Peixoto; Arie Fitzgerald Blank; Maria de Fátima Arrigoni-Blank; Paulo Roberto Gagliardi; Juliana Oliveira de Melo; Daniela Aparecida de Castro Nizio; Vanderson Santos Pinto (Bioscience Journal, 2018)
This work aimed to evaluate the in vitro antifungal activity of the essential oils of L. alba belonging to the carvone chemotype (LA-13 and LA-57) and the citral chemotype (LA-10, LA-29, and LA-44); the carvone enantiomers (R)-(-)-carvone and (S)-(+)-carvone; and citral on phytopathogenic fungi Lasiodiplodia theobromae (LT), Fusarium pallidoroseum (FP) and Fusarium solani (FS). Concentrations of 0.01; 0.05; 0.1; 0.2; 0.3; 0.5 and 1.0 mL/100 mL were tested, and the percentage of mycelial growth inhibition (MGI) was calculated after 96h in relation to the control. Minimal Inhibitory Concentrations (MIC) and Minimal Fungicide Concentrations (MFC) were obtained for essential oils and compounds. From the concentration of 0.2 mL/100 mL, all the accessions and carvone enantiomers were effective against the fungus LT, except the accession LA-44, for which the maximum inhibition occurred from the concentration of 0.3 mL/100 mL. Citral was the most effective compound against LT, with 100% of MGI from the concentration of 0.05 mL /100 mL. All accessions and enantiomers caused 100% of MGI against FP fungus from the concentration of 0.2 mL/100 mL. Once again, citral stood out by providing the same result as the other treatments from the concentration of 0.1 mL/100 mL. Considering the fungus FS, carvone enantiomers and citral caused 100% of MGI from the concentration of 0.1 mL/100 mL while all accessions caused 100% of MGI from the concentration of 0.2 mL/100 mL. Citral and carvone enantiomers presented the lowest MIC values (0.1 mL/100 mL) against FS fungus. The MIC of citral for LT and FP were not determined at the concentrations tested. (R)-(-)-carvone enantiomer presented the lowest MIC (0.1 mL/100 mL) for the LT fungus. Most of the other accessions presented MIC of 0.2 mL/100 mL for the three fungi. In relation to the minimum fungicidal concentration (MFC), citral stood out with values from 0.05 mL/100 mL (LT). Citral and carvone presented the same MFC for FS (0.2 mL / 100 mL). The other accessions showed MFC values from 0.3 mL/100 mL for the three fungi. Essential oils of L. alba accessions, carvone enantiomers, and citral were efficient in phytopathogen control and could be considered as an alternative to fungicides for presenting inhibitory and fungicidal effect against these microorganisms at low concentrations.